2023
DOI: 10.5423/ppj.oa.01.2023.0001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oomycete Activity and Pepper Root Colonization of Pseudomonas plecoglossicida YJR13 and Pseudomonas putida YJR92 against Phytophthora capsici

Abstract: Previously, <i>Pseudomonas plecoglossicida</i> YJR13 and <i>Pseudomonas putida</i> YJR92 from a sequential screening procedure were proven to effectively control Phytophthora blight caused by <i>Phytophthora capsici</i>. In this study, we further investigated the anti-oomycete activities of these strains against mycelial growth, zoospore germination, and germ tube elongation of <i>P. capsici</i>. We also investigated root colonization ability of the bacterial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…(2023) reported that Pseudomonas plecoglossicida RGK exhibits the capacity for hydrogen cyanide (HCN) production. Volynchikova and Kim (2023) demonstrated that P. plecoglossicida suppressed Phytophtora capsici through inhibition of mycelial growth and zoospore germination on M9 minimal medium and V8 juice broth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2023) reported that Pseudomonas plecoglossicida RGK exhibits the capacity for hydrogen cyanide (HCN) production. Volynchikova and Kim (2023) demonstrated that P. plecoglossicida suppressed Phytophtora capsici through inhibition of mycelial growth and zoospore germination on M9 minimal medium and V8 juice broth.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo effect of antagonistic strains on disease severity (%). Fungi (Ali et al, 2020;Höfte, 2021;Kumari et al, 2020), the biocontrol activity of Pseudomonas plecoglossicida, examined in this study, have received limited attention concerning its interactions with plant and pathogen systems (Volynchikova & Kim, 2023). It was originally identified that as a causal agent of bacterial haemorrhagic ascites in ayu fish (Plecoglossus altivelis) (Nishimori et al, 2000), this species is recognized for its pathogenicity towards freshwater fishes such as the large yellow croaker (Pseudosciaena crocea), pejerrey (Odontesthes bonariensis) and rainbow trout (Oncorhynchus mykiss) (Huang et al, 2018).…”
Section: Ta B L Ementioning
confidence: 99%
“…Barley [25] Plant growth promotion Triticum aestivum [56] Antimicrobial activity; plant growth promotion Capsicum annuum [57] Pseudomonas putida…”
Section: Aspergillus Flavusmentioning
confidence: 99%